Modified technique of end to side distal radio-cephalic shunt to overcome juxta-anastomotic stenosis - Atif, Haitham; Zaid, Nehad Abdou; Mohamed, Abd El-Mieniem Fareed; Alkhateep, Yehia Mohamed (International Surgery Journal, 2019)
Background: Juxta-anastomotic stenosis (JAS) is one of the predominant causes of arteriovenous fistula (AVF) failure, with the reported incidence of 65%, so that technical modification to alter the outflow vein configuration using the modified technique has been applied to prevent JAS and improve AVF maturation. The aim of the study to evaluate the modified technique of end-to-side distal radiocephalic A-V fistula regarding maturation, patency rate and the resultant juxta-anastomotic stenosis. Methods: This prospective study was carried out on 80 patients with end stage renal disease (ESRD) at vascular surgery unit in general surgery department, Menoufia university hospital that prepared for dialysis. 40 patients "intervention group" underwent the modified technique to establish a functioning radiocephalic fistula; the other group (40 patients, control group) had the conventional technique of end to side radiocephalic fistula. Follow up of patients was over 6 months regarding function, patency rate and development of juxta-anastomotic stenosis. Results: There was statistically significant difference between 2 groups regarding primary failure, patency and JAS. Primary failure was detected in 2 patients in group A and in 5 patients in group B (p-value is 0.04). Considering patency rate, after 3 months the ratio between group A and group B was 37:34 with significant P value of 0.02, and after 6 months the ratio was 35:33 with P value of 0.03. Regarding JAS, by the end of follow up period, 4 patients diagnosed with JAS in group A, while group B had 8 patients, with p value of 0.01. Conclusions: Modified technique of end to side anastomosis for primary radio-cephalic fistula creation has better patency rate and low incidence of JAS than conventional method.